Regional brain gray matter changes in adolescents with single ventricle heart disease. (5th February 2018) - Singh, Sadhana; Kumar, Rajesh; Roy, Bhaswati; Woo, Mary A.; Lewis, Alan; Halnon, Nancy; Pike, Nancy
Highlights: The study demonstrates gray matter changes in single ventricle heart disease subjects using voxel based morphometry procedure. Single ventricle heart disease showed decreased gray matter in multiple brain sites over control subjects. Study provides structural basis for the mood and cognitive deficits found in single ventricle heart disease. Abstract: Adolescents with single ventricle heart disease (SVHD) show autonomic, mood, and cognitive deficits, indicating aberrations in brain areas that regulate these functions. However, the gray matter integrity in autonomic, mood, and cognitive control sites is unclear. We examined regional brain gray matter changes, using high-resolution T1-weighted images (3.0-T magnetic resonance scanner) with voxel based morphometry procedures, as well as mood and cognitive functions in SVHD (n = 18; age, 15.7 ± 1.1 years; male, 10) and controls (n = 31; age, 16.0 ± 1.1 years; male, 17). High-resolution T1-weighted images were realigned, gray matter tissue type partitioned, normalized to a common space, smoothed, and compared between groups (analysis of covariance; covariates, age and gender). The mood and cognitive scores were compared between groups using independent samples t -tests. SVHD subjects showed significantly altered mood and cognitive functions over controls. Significantly reduced gray matter emerged in multiple brain areas, including the thalamus, caudate nuclei, putamen, insula, prefrontal, post-central and precentral gyrus, occipital gyrus, para-hippocampal gyrus, temporal gyrus, and cerebellar sites in SVHD over controls. SVHD subjects show compromised gray matter integrity in autonomic, mood and cognitive control sites. The findings indicate that frequent deficits found in SVHD subjects have a brain structural basis in the condition.